Trataka Kriya in Individuals with Digital Eye Strain: A Pre–Post Experimental Design - Kumar, K.U. Dhanesh; Shetty, Sparsha; Amin, Hrishikesh; Rashmitha, A. P.; Rani, P. Shilna (Journal of Health and Allied Sciences NU, 2021)
Introduction Digital eye strain is the physical discomfort felt after 2 or more hours in front of a digital screen, including cell phones. Digital eye strain is otherwise known as computer vision syndrome. Trataka is to look at or to gaze—it is a preliminary step for meditation that involves staring at a single point such as a small object, black dot, or candle flame.Objective This study aimed to analyze the effect of trataka kriya in the management of digital eye strain.Materials and Methods Thirty participants of the age group 18 to 40 years were recruited in the study. The study design was a pre–post experiment. A convenient sampling technique was used to recruit the participants. The study included participants who use laptops or smartphones for a minimum of 2 hours daily and also participants having eye strain, dry eyes, burning sensation in the eyes, headache, and eye fatigue. They performed trataka kriya exercises once a day on alternative days for 1 month. Outcome measures was a computer vision syndrome questionnaire to assess the visual fatigue experienced by the study participants and the Schrimer test to find out whether the eye produces enough tears to keep it moist.Statistical Analysis and Results Statistical analysis was done using SPSS version 16.0. To compare the computer vision syndrome questionnaire and Schrimer test before and after interventions paired t-test was used. A p-value of less than 0.05 is considered significant for the study.Conclusion The study concludes that there was an improvement in the subjects with digital eye strain after performing trataka kriya. The clinical implication of the study is that this method can be used as one of the nonpharmacological interventions for digital eye strain.
Keywords: computer vision syndrome; trataka; eye exercises; eye strain; yogic interventions